2010
DOI: 10.1002/sim.3764
|View full text |Cite
|
Sign up to set email alerts
|

A weighted Cox model for modelling time‐dependent exposures in the analysis of case–control studies

Abstract: Many exposures investigated in epidemiological case-control studies may vary over time. The effects of these exposures are usually estimated using logistic regression, which does not directly account for changes in covariate values over time within individuals. By contrast, the Cox model with time-dependent covariates directly accounts for these changes over time. However, the over-sampling of cases in case-control studies, relative to controls, requires manipulating the risk sets in the Cox partial likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…For example, for subjects who alternated periods of high and low levels of exposure, the MIE value was the same whether high levels of exposure occurred either early or later in life. This issue will be further investigated using some recent approaches [35,36].…”
mentioning
confidence: 99%
“…For example, for subjects who alternated periods of high and low levels of exposure, the MIE value was the same whether high levels of exposure occurred either early or later in life. This issue will be further investigated using some recent approaches [35,36].…”
mentioning
confidence: 99%
“…A time-dependent weighted Cox (WC) model has recently been proposed to incorporate this dynamic information on exposure, in order to more accurately estimate the effect of time-dependent exposures in population-based case-control studies [4]. The WC model consists in using age as the time axis and weighting cases and controls according to their case-control status and the age conditional probabilities of developing the disease in the source population.…”
Section: Introductionmentioning
confidence: 99%
“…The weights proposed in the WC model are therefore time-dependent and estimated from data of the source population. A simulation study showed that the WC model improved the accuracy of the regression parameters estimates of time-dependent exposure variables as compared with standard logistic regression with fixed-in-time covariates [4]. However, the average robust sandwich variance estimates based on dfbetas residuals [5] were systematically lower than the empirical variance of the parameter estimates, which resulted in too narrow confidence intervals (CI) and low coverage probabilities [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations